‘Global Harwell’ in an examination-driven education system and an excellence-pursuing society: possible? how? better with digital technologies? - Yu, Fu-Yun; Chan, Tak-Wai; Murthy, Sahana; Wong, Su Luan; Chen, Wenli; So, Hyo-Jeong; Ogata, Hiroaki (Asia-Pacific Society for Computers in Education, 2024)
Under the societal and cultural structure where education systems are heavily driven by examinations (especially in Asia) and the pursuit of excellence reigns supreme, competing for limited educational, environmental/natural, and capital resources is prevalent and appears unavoidable. Although great socioeconomic development and scientific advances have been achieved, it inevitably comes with adverse consequences (e.g., alarmingly increasing rates of anxiety and depression, diminishing learning interest and confidence, social inequity, conflicts, divisiveness, and lack of inclusiveness). The focus of this panel is if and how 'Global Harwell' (a term combining 'harmony' and 'wellbeing') can direct all stakeholders involved in education to a universally shared educational goal. This panel invites a group of international scholars to share their practices and research findings on how the values, principles, concepts, and elements of 'Global Harwell' (e.g., positive emotions, engagement, positive relationships, meaning, accomplishment, compassion, gratitude, empathy) can be or are being actualized in educational systems, with technologies playing a supporting or an essential role at the global, societal, family, and/or individual levels, for ultimate student wellbeing and a harmonious world.